Implementation of Parking Retribution and Illegal Parking Management and Their Effect on Original Local Government Revenue - Muhammad Amin Wattimena; Diana Puturuhu (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2022)
This study aims to determine and analyze the effect of the application of retribution be parking of effect and ilegal parking manajement to against original local government revenue. The determination to  take the number of respondents (sample) in this study was carried out using the census technique. Data recovery was carried out to employees from the central district of the Moluccas transportation agency with a population of 40 respondents. The collected data were analyzed by multiple linear regression analysis. The result shows that implementation retribution be parking of effect to against original local government revenue. The results of testing proved that all hypotheses in this study were accepted.